Requirements for an EMR-Based Virtual Reality Application for PROLANIS Education: A Literature and Process-Mapping Synthesis - Setya Wijayanta; Adhani Windari; Mochammad Arief Darmawan; Sylvia Anjani; Faik Agiwahyuanto (Jurnal Infokes, 2026)
Background: PROLANIS participants require repeatable chronic-disease education, while electronic medical records (EMRs) and virtual reality (VR) offer opportunities for personalized and interactive delivery. Before prototype development, requirements must reflect health literacy, workflow, privacy, and VR safety. Methods: This descriptive initial Research and Development stage used a literature- and document-informed requirements synthesis, a proposed PROLANIS process map, and minimum EMR data-element mapping for Sidorejo Lor and Sidorejo Kidul Community Health Centers, Salatiga City. No interviews, focus-group discussions, participant surveys, direct observations, or patient-level EMR extraction were conducted at this stage. Candidate requirements were organized into domains and provisionally prioritized using MoSCoW as design input requiring later stakeholder validation. Results: Five preliminary requirement groups were identified: concise chronic-disease education, EMR-based personalization, adult- and older-user accessibility, data security and confidentiality, and operational support for health workers. Proposed must-have functions include a patient education profile, simple visualization of examination results, and hypertension and diabetes modules. Non-functional requirements include simple navigation, large text, audio narration, seated mode, short sessions, stop/pause options, and role-based data access. Conclusion: The study provides an initial, literature- and process-mapping-based requirements model rather than empirically validated local user needs. Participatory co-design, stakeholder validation, usability testing, VR-safety assessment, data-governance review, and evaluation of patient understanding are required before implementation claims can be made